Edukasi dan Praktik Penanggulangan Stunting bagi Ibu Balita Stunting di Desa Lokus Stunting Kabupaten Banyumas - Ika Pantiawati; Widya Ratna Wulan; Evina Widianawati; Tiara Fani; Nurrisa Ananda (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to improve the knowledge, attitudes, and behavior of mothers of toddlers regarding stunting prevention. The method for implementing this service used assistance and practice carried out on mothers who had stunted toddlers in Lokus Stunting Village, Banyumas Regency. Detailed activities included preparation, pre-test, checking toddler growth and development, providing education, practice of cooking MP ASI, and post-test. The evaluation instrument for this activity used a questionnaire and was analyzed descriptively. The results of this service showed that above-average participants experienced an increase in knowledge after training by 6%, indicating that participants' knowledge increased compared to before mentoring. The attitude aspect after mentoring also increased by 17%, and the practical aspect increased by 3%.